The Diverse Impacts of the Neo-liberal Social Policies on Children's Welfare and Social Work with Young People: The Finnish Perspective - Mirja Satka (Social Work and Society, 2007)
This article discusses the impacts of globalization, neo-liberal social policies and the Finnish economic recession of the 1990s on children's and young people's welfare. It summarises some of the impacts of Finnish social policies on the everyday lives of families with children and highlights some of the features of the recent and current debates surrounding youth delinquency and the societal reactions to young generations. All this contributes to a contradictory and conflicting societal context which challenges experts in the field of child welfare social work experts to operate - as expected - at the right moment, legally and effectively. Instead of being overly-defensive for the 'good old' ways of practicing social work with children, the authors invite social work scholars and practitioners to reconceptualise both the concept of children's citizenship and its position both in child welfare theory and practice in the context of children's global rights.